Pengembangan Modul Praktikum Kimia SMA Berbasis PBL(Problem Based Learning) - Desy Rosmalinda; Muhammad Rusdi; Bambang Hariyadi (Universitas Jambi, 2013)
The research was intended to develop a simple practical guide and pieces of science process skills and scientific attitude of students assessment. Development model used was ADDIE, which stands for Analysis, Design, Development, Implementation and Evaluation. The model used in the lab module was problem based learning, which students were given problems before practicum began. Subjects of trials in this study consisted of six students were grouped into three categories of cognitive abilities, smart students, middle students and weak students. Results of product trials indicated that all students responded positively to the lab module. Modules can be applied to students with diverse cognitive abilities, the weak cognitive students could need teacher guidance, especially in the matter of analysis to understand.